2011
DOI: 10.1152/ajpgi.00078.2011
|View full text |Cite
|
Sign up to set email alerts
|

The role of dystroglycan in PDGF-BB-dependent migration of activated hepatic stellate cells/myofibroblasts

Abstract: This extracellular matrix contains several basement membrane components including laminin, but its composition changes during liver injury because of the production of extracellular matrix components found in scar tissue. These changes in extracellular matrix composition and in cell-extracellular matrix interactions may play a key role in hepatic stellate cell transdifferentiation. In this communication we used early passages of mouse hepatic stellate cells (activated HSC/ myofibroblasts) to study the platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
(29 reference statements)
0
11
1
Order By: Relevance
“…This finding supports our result that enhanced expression of hepatic SATB1 mediated the synthesis of CTGF. PDGF-A and PDGF-B and their receptors are expressed in liver myofibroblasts, PDGFs could stimulate the migration and proliferation of stellate cell, mediated inflammation and fibrogenesis during the liver injury4041. In addition, HBx induced IL-6 production in hepatocytes and hepatoma cells, IL-6 could trigger hepatic cells proliferation and liver regeneration, and modulate synthesis of collagen I42.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports our result that enhanced expression of hepatic SATB1 mediated the synthesis of CTGF. PDGF-A and PDGF-B and their receptors are expressed in liver myofibroblasts, PDGFs could stimulate the migration and proliferation of stellate cell, mediated inflammation and fibrogenesis during the liver injury4041. In addition, HBx induced IL-6 production in hepatocytes and hepatoma cells, IL-6 could trigger hepatic cells proliferation and liver regeneration, and modulate synthesis of collagen I42.…”
Section: Discussionmentioning
confidence: 99%
“…TGFBR2: −2.26 times in HSC-T6 + CDCA and −12.2 times in HSC-T6 SHP) (Table 3). Of relevance, six of these 46 DEGs (CXCL12, TGFBR2, DAG1, GR, NCoR and Rb1) are mechanistically involved in the activation and trans-differentiation of HSC15161718192021.…”
Section: Resultsmentioning
confidence: 99%
“…Although we also found that F/P-MPs coating suppressed the contour alterations of RI-T cells and the mRNA expression of collagen type IαI and TGF-β1 in activated HSCs, we observed that the expressions of α-SMA and TIMP-1 were not suppressed by cultivation on F/P-MPs plates or on Matrigel plates. This result indicates that F/P-MPs can partially inhibit RI-T activation, which may be based in part on differences in cell characteristics (for example, there might be a fibronectin receptor expression difference between RI-T and primary HSCs), because Matrigel contains fibronectin, which affects HSC activation [13].…”
Section: Discussionmentioning
confidence: 96%